Combination treatment with valsartan and amlodipine intensifies evening suppression of Bmal1 clock gene in kidneys of spontaneously hypertensive rats - Potucek P.; Radik M.; Doka G.; Kralova E.; Krenek P.; Klimas J. (Sciendo, 2017)
Blood pressure (BP) rhythm is exhibited in a circadian pattern regulated by complex system of endogenous factors. Administration of pharmacological treatment at the right time can influence the efficacy of treatment; but while kidneys play significant role in BP regulation, little is known about their role in chronopharmacotherapy. This study aimed to compare differences between morning and evening dosing with valsartan and amlodipine combination in both short-term and long-term settings and to elucidate the role of kidneys in chronopharmacology. Spontaneously hypertensive rats aged between 8 and 10 weeks were daily treated with 10mg/kg of valsartan and 4 mg/kg of amlodipine, either in the morning or in the evening with treatment duration of 1 and 6 weeks. After short-term treatment, only morning treatment group demonstrated significantly better outcomes in terms of BP control when compared to placebo. After long-term treatment, both treatment groups gained superior results in BP control against placebo; however, no significant difference was seen between morning and evening treatment. Interestingly, clock gene expression in kidney has been significantly modulated only in the evening-treated groups, with treatment intensifying the reduced Bmal1 levels, while Per2 expression was less altered. However, no direct relation with the outcomes of the therapy has been observed, suggesting that pharmacotherapy may serve as an independent modulator of peripheral circadian clock in the kidney.